Explanation of Mystical Hermeneutics in Ja'far al-Sadiq's Exegesis Based on Paul Ricoeur's Opinions - Reza Tabatabaee Amid; Ghodratollah Khayatian; Azim Hamzeian (مطالعات زبانی و بلاغی)
An exegesis of the Qur'an published by Paul Nwyia is attributed to Ja'far al-Sadiq. Paul Ricoeur, French philosopher and literary man, is one of the most remarkable theoretician of literary and philosophical hermeneutic. In this research, referring to the hermeneutics of the Ricoeur and its characteristics, Ja'far al-Sadiq's exegesis is investigated. The mystical hermeneutics of Ja'far al-Sadiq's interpretation are almost in accordance with the hermeneutics of Ricoeur. Interpretation and polysemy in mystical exegeses start with this interpretation. Everyone understands the words and verses of the Qur'an according to his degree of understanding and aspect of being. Based on Ricoeur, metaphor and symbolism are abundant in this exegesis, while myths can only be found about the angels and the Fall of Adam. Stories follow the rules that Ricoeur has expressed for narrative hermeneutics. Ricoeur believes that all interpretations are rightful, but in Islamic mysticism, absurd interpretation of verses is not acceptable.